Modern Methods of fatigue assessment - Volkova, Y. (Slobozhanskyi herald of science and sport, 2020)
Purpose: to determine the general and modern methods of fatigue assessment. Materials and methods: analysis and generalization of scientific and methodical literature on the topic of study of fatigue processes; generalization of experience of practical work of the coaching contingent working with children in groups of dancesport; modified method of M.Ya.Breitman`s clinical anthropometry; natural pedagogical experiment, methods of mathematical statistics and mathematical modeling. Results: it should be noted that the improvement of information technology and the use of more efficient electronic devices allows for more promising development of mathematical modeling, provided its application in theoretical and practical studies of various processes in the human body, including processes such as fatigue. Therefore, in the further process of diagnosing the stages of fatigue, it is possible to apply mathematical models that already exist, as well as to continue the search for other options (in particular, using the theory of self-organizing systems). Conclusions: the application of existing theories of fatigue makes it possible to consider the variety of causes of fatigue in the human body in terms of physiology. Understanding the causes of the fatigue process allows to develop systems that can restore the human body, using the possibility of additional feeding with the necessary substances for activity or imposing restrictions on the intensity and timing of actions. For more effective diagnosis of the degree of fatigue process, it is possible to usemethods of mathematical modeling and forecasting, as well as consideration of the fatigue process in terms of stability of selforganizing systems (including applying the Volterra equations, flow cultivator). Modern research methods of using mathematical apparatus and information tools allow for better and faster processing and analysis of large data sets.